Konsep Dasar Kesehatan Mental(Pengertian, Prinsip-Prinsip, Fungsi Mental Hygiene) - Ardiva Morlindah Tripertiwi (Educazione: Jurnal Multidisiplin, 2025)
Nowadays we often find individuals who experience anxiety disorders, fear and other negative feelings, this condition certainly has a cause and there is a root cause for that in this article the author will discuss what is the meaning, principles, and functions of mental health. Where the hope is that through this article the reader can take advantage of themselves so that they can understand the importance of mental health to live their daily lives. Subjective factors in determining the concept of healthy and sick are contained in the understanding of health in Law No. 9 of 1960 concerning the principles of health, it is stated that "Health is that which includes physical, spiritual (mental), and social health, and not only a condition free from disease, disability, and weakness". Mental Health is mental health is the ability to adjust to oneself, to others and the community and the environment in which one lives. In fact, peace of life, peace of mind or inner happiness, does not depend much on external factors such as social, economic, political, customary and so on: but rather depends more on the way and attitude of dealing with these factors. Zakiah Daradjat is a Muslim psychologist. In addition, he also has extraordinary attention to Islamic education. Because Zakiah Daradjat's educational background is in psychology, her educational thinking tends towards mental education, especially mental health. The existence of such a tendency of thinking seems to be a significant difference from other Islamic educational thinkers. For Zakiah Daradjat, Islamic education has a clear and definite goal. According to Zakiah, Islam has a clear and definite goal, namely to foster humans to become pious servants of Allah with all aspects of their lives that include actions, thoughts, and feelings. As for the method of this article, the author uses a type of library research, namely a series of activities related to the method of collecting library data. namely a series of activities with the method of collecting library data in order to obtain data information by collecting information related to the Definition, Principles and Functions of Mental Health. In this study, the author uses a content analysis approach model (content study), this research is a deep discussion of written or printed information in the mass media which is used to draw conclusions through efforts to find message characteristics, and is carried out objectively and systematically. The results of this study are the importance of understanding mental health and the principles contained therein and its functions for humans who are constantly in the process of growing and developing into complete human beings.